Development of all-in-one CRISPR/Cas9 and CRISPRi AAV constructs to treat autosomal dominant retinitis pigmentosa - Peddle, CF (2021)
Dominant mutations in RHO (rhodopsin) are the most common cause of autosomal dominant retinitis pigmentosa (RHO-adRP). RHO-adRP causes progressive loss of rod cells, followed by cone cells, leading to blindness. This disease is a candidate for CRISPR gene editing, as reduction of mutant rhodopsin is associated with phenotypic rescue. This thesis optimises all-in-one CRISPR/Cas9 and CRISPRi adeno-associated viruses (AAVs) and explores their potential as RHO-adRP gene therapy vectors. Following construct optimisation in vitro, a CRISPR/Cas9 and CRISPRi plasmid carrying SaCas9 and dSaCas9.KRAB, respectively, were generated. Both demonstrated knock down of endogenously expressed EGFP in a transgenic cell line. For allele-specific knock down of RHO, the CRISPR constructs must target a region unique to the mutant allele. Bioinformatic screening of RHO identified seven non-pathogenic single nucleotide polymorphisms (SNPs) that were targetable with SaCas9. Two of these SNPs could be targeted allele-specifically, with high CRISPR/Cas9 gene disruption and CRISPRi gene repression rates of 38.5-73.2 % and 43.1-65.8 %, respectively. In heterozygous patients, targeting the SNP on the mutant RHO offers a mutation-independent allele-specific targeting strategy. As a proof-of-concept for targeting rod cells, the AAV were subretinally injected into Nrl-EGFP mice, in whom enhanced green fluorescent protein (EGFP) expression is limited to rod photoreceptors. To restrict Cas9 expression to rods cells only, a novel 154 bp rod cell-specific promoter was identified. This shortened promoter from the PDE6B gene was active in human retinal explants, the human retinoblastoma-derived cell line Y79, and drove strong rod cell-specific expression in mice. The CRISPRi AAV was unable to repress EGFP, despite high transgene expression. The CRISPR/Cas9 AAV however, drove strong EGFP disruption. It produced 4.1 % EGFP indels, resulting in a reduction of EGFP mRNA and fluorescence of 55.3% and 36.5 %, respectively. The all-in-one CRISPR/Cas9 AAV is therefore able to drive strong gene disruption in rod cells in vivo, making it a useful vector for the treatment of RHO-adRP. This thesis describes in detail the development of these all-in-one CRISPR/Cas9 and CRISPRi AAV vectors from proof-of-concept to in vivo study and advances the potential for using such therapies in future treatments of RHO-adRP.